Issues on Modern Tendencies in Teaching Intercultural Communication - Adilova Fotima Muhammadanasovna (International Journal on Integrated Education, 2022)
The article deals with the issues based on contemporary tendencies in teaching intercultural communication. As we know, a future specialist in intercultural communication should be thoroughly prepared to participate in professional business international cooperation and be able to take into accounting the specific ideas and preferences existing in the cultures of foreign business partners in the ways of forming thoughts. In this regard, in professionally oriented teaching of foreign language communication of students of language faculties, special attention should be paid to the development of their ability to choose the correct form to formulate their ideas, taking into account the cultural identity of the native speaker. This is another of the current trends in teaching intercultural communication in the system of higher language education.